Analisis Teologi Pendidikan Dalam Penguatan Pendidikan Islam - Muhidin Muhidin; Ahmad Nurwadjah; Andewi Suhartini (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Education is often interpreted as a conscious effort made by educators towards students in an effort to provide knowledge, education and teaching to achieve happiness and the ultimate goal of life. The purpose of the true happiness of life is that which includes the fulfillment of physical and spiritual aspects. Islam as a doctrinal force has the essence of both. Education in Islam is education that is based on the teachings of Islam, Islam as a religious teaching taught and brought by Muhammad SAW, contains a set of teachings about human life, teachings that are formulated based on sources in the Qur'an and hadith and based on the explanation of the ratio of reason. So that the realization and reinforcement obtained in Islamic education must include physical and spiritual aspects